2008
DOI: 10.1093/nar/gkn439
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Adriamycin–DNA adducts by accelerator mass spectrometry at clinically relevant Adriamycin concentrations

Abstract: Limited sensitivity of existing assays has prevented investigation of whether Adriamycin–DNA adducts are involved in the anti-tumour potential of Adriamycin. Previous detection has achieved a sensitivity of a few Adriamycin–DNA adducts/104 bp DNA, but has required the use of supra-clinical drug concentrations. This work sought to measure Adriamycin–DNA adducts at sub-micromolar doses using accelerator mass spectrometry (AMS), a technique with origins in geochemistry for radiocarbon dating. We have used conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 60 publications
3
61
3
Order By: Relevance
“…DNA adducts are common injuries that can be induced by the mutagenic agents used in this work, 38,39,42,49,50 and despite of the different primary type of DNA lesions induced, we showed that cisplatin, doxorubicin, HN2 and MMS are able to generate DNA fragmentation (Fig. 5).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…DNA adducts are common injuries that can be induced by the mutagenic agents used in this work, 38,39,42,49,50 and despite of the different primary type of DNA lesions induced, we showed that cisplatin, doxorubicin, HN2 and MMS are able to generate DNA fragmentation (Fig. 5).…”
Section: Resultsmentioning
confidence: 61%
“…DNA strand breaks after cisplatin, doxorubicin, HN2 and MMS exposure can be formed as a consequence of DNA repair and/or replication processes. [36][37][38][39][40] Nek1 and Nek11 human proteins have been shown to be involved in the response to DNA double strand breaks (DSB). 17,[20][21][22] In order to verify if our treatment induces breaks in DNA and the possible involvement of Kin3 in this response, likewise the case of human Neks, we performed an alkaline gel electrophoresis that detects DNA fragmentation, as consequence of single and double deleted cells have an increased sensitivity to cisplatin, doxorubicin, HN2 and MMS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For measuring biological samples, the most relevant isotopes are 14 C and 3 H. The sensitivity of AMS is high enough that even very small amounts of exogenously applied radioisotopes can be detected, thereby allowing AMS to be used in human studies. 47 The sample preparation protocol involves the extraction of cellular DNA which can be either analyzed as intact DNA or subjected to enzymatic digestion into nucleotides. This is followed by the separation with HPLC to isolate the adduct of interest.…”
Section: Accelerated Mass Spectrometry (Ams)mentioning
confidence: 99%
“…The mechanism of DOX was controversial. It is still broadly investigated by many research groups including ours [18] [19]. In our former work, we have screened the targets of DOX by high density protein array which contains 17,950 kinds of proteins [20].…”
Section: Introductionmentioning
confidence: 99%